1986
DOI: 10.1016/s0140-1971(86)80029-x
|View full text |Cite
|
Sign up to set email alerts
|

The importance of peer group (“crowd”) affiliation in adolescence

Abstract: Many researchers have speculated about the role peer groups play in adolescent development, but few have examined teenagers' own perspective on the importance of group affiliations. The two studies reported here, involving 1,300 7th to 12th graders in three Midwestern U.S. communities, assessed teenagers' valuation of belonging to a “crowd” as well as the reasons they cited to support or oppose crowd affiliation. The importance of crowd affiliation declined across age. Younger adolescents generally favored mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
174
1
11

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(195 citation statements)
references
References 12 publications
9
174
1
11
Order By: Relevance
“…Numerous studies have shown that young adolescents consider their peers as more significant in their lives and are less attached to their parents as they grow older although crowd affiliation declines as adolescents grow older, being more interested in their personal identity (Brown, Eicher & Petrie, 1986). Therefore, in general, peer influence on students' motivation in the college classroom has been less explored, and the specific concept of peer enthusiasm in the classroom has not been studied in field of peer influence or classroom climate.…”
Section: Peer Enthusiasmmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that young adolescents consider their peers as more significant in their lives and are less attached to their parents as they grow older although crowd affiliation declines as adolescents grow older, being more interested in their personal identity (Brown, Eicher & Petrie, 1986). Therefore, in general, peer influence on students' motivation in the college classroom has been less explored, and the specific concept of peer enthusiasm in the classroom has not been studied in field of peer influence or classroom climate.…”
Section: Peer Enthusiasmmentioning
confidence: 99%
“…For instance, the peer group can refer to an individual's relatively close group of friends who interact rather regularly, or to a clique (Brown, 1990). In some articles, peer group and crowd have been used interchangeably (Brown, Eicher, & Petrie, 1986). In Ntoumanis and…”
Section: Peer Enthusiasmmentioning
confidence: 99%
“…For example, Brown and colleagues have constructed a developmental model of peer group affiliation that locates adolescents within a complex network of social crowds (e.g., druggies/burnouts, brains, preppies, nerds) that are both relational and reputational in nature (Brown et al, 1986;Brown et al, 1994). Although the constellation of crowds varies somewhat, virtually all extant models of adolescent crowd affiliation have prominently featured the "jock" crowd, sometimes in isolation and sometimes as part of a larger elite or "popular" group.…”
Section: Jock Identity Vs Athletic Participationmentioning
confidence: 99%
“…The bullying literature on typically developing youth indicates that peer victimization experiences are related to poor parent-child relationships (Spriggs, Iannotti, Nansel, & Haynie, 2007;Ybarra & Mitchell, 2004). Because peers have such a critical socialization role during childhood and adolescence (Brown, Eicher, & Petrie, 1986), peer relationships are likely implicated in the consideration of risks and protective processes related to victimization. Researchers have found that poor peer relationships place youth at risk for victimization, while having close friends protects against victimization within the general population (Delfabbro et al, 2006;Forero, McLellan, Rissel, & Bauman, 1999;Nansel et al, 2001;Pellegrini & Bartini, 2000;Pellegrini, Bartini, & Brooks, 1999;Williams & Guerra, 2007).…”
mentioning
confidence: 99%